Mexico : Financial Sector Assessment - World Bank (Washington, DC, 2013)
The report is based on the joint International Monetary Fund-World Bank Financial Sector Assessment Program (FSAP), and summarizes the quantitative data through end-2000, although the quantitative discussion in this report has been updated to reflect salient developments since then. The FSAP took place at an important juncture for the development of the financial sector, with major legal reforms being introduced, which for the most part, were consistent with FSAP recommendations. Consequences of the 1994/95 banking crisis have been absorbed, with the associated fiscal losses transparently allocated to the public sector, in the form of explicit IPAB (Instituto de Proteccion de Ahorros Bancarios) debt. Macroeconomic indicators strengthened significantly since the crisis, due to the improved policy management, and closer links to the US economy. However, while the policy of increasing the share of domestic public sector debt has gains in terms of reduced vulnerability, it is not without costs, for regulations discourage loan dollarization, and limit systemic liquidity risks, but may lead to lower credit, and higher lending spreads. The Government is active in the financial system through a large network of development banks (DBs), and funds, entailing a significant burden, in many cases, hampering market development. Thus, a reform strategy to overcome tensions should aim at separating subsidies from finance, at consolidating DBs, and at gradually transforming some DBs into development agencies. This report further looks at private banking system trends, performance and stress testing, at state ownership in financial intermediation, and at policy issues in prudential regulation, securities market development, and the insurance sector.